Digitalisasi Dan Filsafat Ilmu Dalam Pembelajaran PAI Di SMK Bustanul ‘Ulum Kabupaten Bandung - Susanto, Heri Rahmat; Irawan; Priatna, Tedi (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Digitalization in Islamic Religious Education (PAI) learning has opened new opportunities to create more effective, interactive, and relevant teaching methods for contemporary needs. This study aims to explore the experiences, perceptions, and challenges faced by teachers, students, and school management in implementing digitalization in PAI learning at SMK Bustanul ‘Ulum, Bandung Regency. Employing a qualitative phenomenological approach, data were collected through in-depth interviews with research subjects. The findings reveal a strong commitment from the school to integrate technology through clear policies, supporting facilities, teacher training, and digital ethics guidelines. Teachers and students positively embrace digitalization despite challenges such as infrastructure limitations and digital literacy gaps. The philosophy of science perspective underscores the importance of aligning technology usage with Islamic values, ensuring that digital-based learning not only creates engaging experiences but also focuses on character and moral development. This study aims to provide theoretical and practical insights for designing ethical, value-oriented technology-based religious education relevant to the digital era.